Re-engineering the Agro-forestry Park: the case of Malaysia Agriculture Park Bukit Cahaya Seri Alam Shah Alam, Selangor / Samsida Mat Salleh … [et al.] - Mat Salleh, Samsida; Shariff, Wahida; Mohamad, Shahnaz Haris; Faisal, Rizal Fariz (2005)
Tourism has become a potential growth industry which contributes the largest in services receipts and third largest foreign exchange earner to the country. The strong performance of the tourism industry is reflected by the increase in number of tourist arrival to Malaysia. In 1987, the Ministry of Agriculture has taken the initiative to introduce and develop the idea of agriculture activities as one of the tourism industry. Further to this, Ministry of Agriculture has developed a forest with the concept of agro-forestry known as Malaysia Agriculture Park (MAP), Bukit Cahaya Seri Alam, Shah Alam Selangor. At initial stage, MAP was well accepted by the public which managed to attract about 500,000 visitors a year. However, the numbers of visitors began to decline greatly since 1993, where the park only received 98,147 visitors in 2004. Due to the concern of this continuing declining number of visitors and other factors such as abandoned and unattractive facilities and attractions, lack of resources and negative customers' perception on the park has lead the researchers to undergo the study on "The Reengineering of Agro-Forestry Park : The Case of Malaysia Agriculture Park" with the objectives to establish the current status of MAP, to reengineer MAP to be preferred tourism destination and to suggest appropriate business strategies in order to achieve MAP's founding vision and mission. In achieving the objectives, the researcher has develop the academic construct model which is used to ensure that the determined objectives are achieved. The model comprises the evaluation of the current status of MAP that is the corporate audit, the key success factors, the reengineering process and business strategy for MAP.